Profile of Problem Solving System of Linear Equations Two Variables of MTs Al-Khairat Tomini Students Based on Student Learning Styles - Raiyan, Raiyan; Sukayasa, Sukayasa; Anggraini, Anggraini; I Nyoman Murdiana, I Nyoman Murdiana (Universitas Sembilanbelas November Kolaka, 2023)
This research aims to obtain a description of the problem-solving profile of two-variable linear equation systems of MTs Al-Khairat Tomini students based on the student's learning styles. This type of research is qualitative. The subjects of this research were three students in class VIII B MTs Al-Khairat tomini, each consisting of one student with visual, auditory, and kinesthetic learning styles. Data on student problem-solving was obtained from written tests and interviews. This research shows that the subject (IN) carries out the problem-solving plan by the solution plan questions, and the subject did not recheck the problem-solving because he did not understand how to do it. The subject (MA) carries out the problem-solving plan by the problem-solving plan, and the subject can check and solve questions by checking the written answers again.